Antimicrobial activity screening of fungal endophytes isolated from scleria sumatrensis retz. (Family : cyperaceae) at UNIMAS east campus - Tan, Ting Ting (Universiti Malaysia Sarawak, UNIMAS, 2010)
The increasing prevalence of multiple drug resistant bacteria has posed serious global health problems. This trend has rendered the discovery of new antibiotics to become indispensable. Because fungal endophytes have been recognised as potential sources of antibiotic, a study was carried out on endophytes of wild grass, Scleria sumatrensis Retz. In this study, fungal endophytes were isolated from the stems of the grass and then screen for the presence of antibiotics. Two stages of preliminary antibacterial testing were carried out via agar overlay technique using PDA and V8 juice agar, respectively. In preliminary antibacterial screening, the isolate E5b1 was found to be active against three test bacteria which were Staphylococcus aureus, Enterobacter aerogenes and Escherichia coli. The isolates E1a1, E1a3 and E5a1 were active against two test bacteria which were S. aureus and E. aerogenes, whereas the isolate E3b1 was only active against E. aerogenes. The active secondary metabolites of the five endophyte isolates were extracted with methanol and were evaluated for antibacterial activity by using Kirby-Bauer disc diffusion method. The methanol extracts of isolates E1a1, E1a3, E3b1 and E5a1 showed antibacterial activity toward at least one test bacteria which were either S. aureus, E. aerogenes or both. However, the methanol extract of isolate E5b1 did not show antibacterial activity towards all four test bacteria. Identification of the endophyte isolates to the genus level was predominantly based on the microscopic observations. The genus of isolates E1a1, E1a3, E5a1 and E5b1 were Phialophora, Gilmaniella, Cacumisporium and Endophragmia, respectively, whereas isolate E3b1 was recognised as sterile mycelia since it was unable to produce spores under the culture condition. Further study on the secondary metabolites of fungal endophytes should be conducted due to its high potential in medical application.